Genomic Adaptations to an Endoparasitic Lifestyle in the Morphologically Atypical Crustacean Sacculina carcini (Cirripedia: Rhizocephala). (12th October 2022) - Martin, Sebastian; Lesny, Peter; Glenner, Henrik; Hecht, Jochen; Vilcinskas, Andreas; Bartolomaeus, Thomas; Podsiadlowski, Lars
Abstract: The endoparasitic crustacean Sacculina carcini (Cirripedia: Rhizocephala) has a much simpler morphology than conventional filter-feeding barnacles, reflecting its parasitic lifestyle. To investigate the molecular basis of its refined developmental program, we produced a draft genome sequence for comparison with the genomes of nonparasitic barnacles and characterized the transcriptomes of internal and external tissues. The comparison of clusters of orthologous genes revealed the depletion of multiple gene families but also several unanticipated expansions compared to non-parasitic crustaceans. Transcriptomic analyses comparing interna and externa tissues revealed an unexpected variation of gene expression between rootlets sampled around host midgut and thoracic ganglia. Genes associated with lipid uptake were strongly expressed by the internal tissues. We identified candidate genes probably involved in host manipulation (suppression of ecdysis and gonad development) including those encoding crustacean neurohormones and the juvenile hormone binding protein. The evolution of Rhizocephala therefore appears to have involved a rapid turnover of genes (losses and expansions) as well as the fine tuning of gene expression.